Connecting the dots of care: survey of Australian hospital pharmacy departments regarding current initiatives in place to care for Aboriginal and/or Torres Strait Islander inpatients. (8th March 2022) - Welch, Susan; Patel, Bhavini; Williams, Aleena; Moles, Rebekah
Abstract: Introduction: There are limited data describing the role of hospital pharmacists caring for Aboriginal and/or Torres Strait Islander inpatients. Objectives: To determine roles of and specific services provided by Australian Hospital pharmacists/Pharmacy Departments in providing medicine management services to Aboriginal and/or Torres Strait Islander people admitted to Australian hospitals. The actual and perceived outcomes will be explored. Method: Mixed method (online survey/ telephone semi‐structured interviews). The survey was emailed to all Directors of pharmacy departments listed in The Society of Hospital Pharmacists of Australia Directory (January 2019). Participants were invited for a digital, audio recorded follow‐up telephone interview. Recordings were transcribed verbatim and thematically analysed. Results: Sixty‐nine responses were received from 313 pharmacy departments (RR = 22%), of these, 20 (29%) pharmacists agreed to and underwent a semi‐structured interview. All hospital categories, states and territories were represented: Metropolitan (33, 48%); regional (22, 32%); rural (12, 17%) and remote (2, 3%). Over half (44, 64%) had specific processes for Aboriginal and/or Torres Strait Islander inpatients. Service outcome measurement was low (10, 14%). Survey results and qualitative interviews revealed work is being done under the broad themes: culturally safe care; provision of culturally appropriate medicines information; chronic disease management; continuum of care; managing funding models. Potential outcome measures and future plans were proposed. Conclusion: Several sites have pharmacy services in place specifically for Aboriginal and/or Torres Strait Islander people admitted to hospital which are not included in the literature; however, outcomes of these services were not routinely assessed. The challenges faced are similar to those cited in international literature, including managing continuity of care issues and working in partnership on projects tailored to the needs of Indigenous peoples. Wider knowledge, evaluation and measurement of the impact of these services on health outcomes and equity is needed and would allow hospital pharmacy teams to better tailor initiatives to meet the needs of Aboriginal and/or Torres Strait Islander people.